O sistema de precedentes como método para controle do excesso de demandas - Siqueira, Leonardo Cortez Casol (2019)
Keeping in mind the current phase of the Brazilian legal system, with thought of members of the Judiciary in constant evolution, together with the amendment of certain procedural laws, the judicial activity is entering a very important moment of internal legitimation. It is becoming necessary for judges to seek more and more to apply a dynamic, swift and egalitarian Right. The purpose of this study, then, is to reflect on the large number of ongoing lawsuits in the country. Within the line of research "Justiça e o Paradigma da Eficiência", through which this work proposes to verify how are the procedures for application of the System of Precedents, the ‘Incidente de Resoulução de Demandas Repetitivas’ and other mechanisms implicit in the Civil procedural law, as the ‘Incidente de Assunção de Competência’. In addition to these which, in a less obvious way, were also created to contain the advances of unnecessary demands, such as ‘sucumbência recursal’ and the requirement of deposit prior to joining with ‘ação rescisoria’. The research technique is the bibliographical one, under a deductive approach on the subject, adhering to the context that it is possible to reach a procedural adequacy, so that the Judiciary maintains a uniform and fluid control standard on its decisions, giving focus to the procedural guidelines to assist in this regard.